2020
DOI: 10.3390/cells9112360
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-Associated Neurological Disorders: The Potential Route of CNS Invasion and Blood-Brain Barrier Relevance

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a novel human coronavirus that has sparked a global pandemic of the coronavirus disease of 2019 (COVID-19). The virus invades human cells through the angiotensin-converting enzyme 2 (ACE2) receptor-driven pathway, primarily targeting the human respiratory tract. However, emerging reports of neurological manifestations demonstrate the neuroinvasive potential of SARS-CoV-2. This review highlights the possible routes by which SARS-CoV-2 may invade th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
136
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(153 citation statements)
references
References 134 publications
(172 reference statements)
1
136
0
9
Order By: Relevance
“…It is a human coronavirus (HCoV) in the beta genera of the coronaviridae family, along with severe acute respiratory syndrome coronavirus-1 (SARS-CoV-1), Middle East respiratory syndrome related coronavirus (MERS-CoV), HCoV-OC43, and HCoV-KHU1 [ 10 ]. During cell entry, SARS-CoV-2 binds angiotensin converting-enzyme 2 (ACE2) on the target cell surface to facilitate fusion of viral and host membranes [ 11 , 12 ]. ACE2 exists on cellular membranes in the lungs, gastrointestinal (GI) track, myocardium, renal tubules, and bladder [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is a human coronavirus (HCoV) in the beta genera of the coronaviridae family, along with severe acute respiratory syndrome coronavirus-1 (SARS-CoV-1), Middle East respiratory syndrome related coronavirus (MERS-CoV), HCoV-OC43, and HCoV-KHU1 [ 10 ]. During cell entry, SARS-CoV-2 binds angiotensin converting-enzyme 2 (ACE2) on the target cell surface to facilitate fusion of viral and host membranes [ 11 , 12 ]. ACE2 exists on cellular membranes in the lungs, gastrointestinal (GI) track, myocardium, renal tubules, and bladder [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Moriguchi et al [ 48 ] observed viral RNA in the cerebrospinal fluid of a patient with aseptic encephalitis and Paniz-Mandolfi et al [ 49 ] reported the presence of SARS-CoV-2 viral particles in the neuronal and capillary endothelial cells in the frontal lobe tissue in a postmortem study. It has therefore been suggested that SARS-CoV-2 neuroinvasion, neuroinflammation and impairment of the blood–brain barrier (BBB) are responsible for the neurological symptoms [ 50 ].…”
Section: Pathogenesis Of Neuro-covidmentioning
confidence: 99%
“…More than a third of patients with COVID-19, especially those with severe to critical COVID-19 who managed on an intensive care unit (ICU) develop central nervous system (CNS) symptoms and signs (e.g., headache, dizziness, ataxia, seizure, delirium, confusion, impaired consciousness) consistent with CNS involvement and /or neurological complications (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Cerebrovascular complications of viral sepsis, including ischemic or hemorrhagic stroke, CNS involvement in CRS, hypoxia as well as the interplay of comorbidities have been implicated as contributing factors (6)(7)(8)(9)(10)(11)(12)(13). Due to the neuro-invasive capability of SARS-CoV-2, acute disseminated encephalomyelitis (ADEM) and viral encephalitis have also been suspected in some patients (13).…”
Section: Introductionmentioning
confidence: 99%